2016
DOI: 10.5223/pghn.2016.19.3.162
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Impacts of Gluten-Free Diet among Saudi Children with Celiac Disease

Abstract: PurposeTo determine the socio-economic impact of gluten free diet (GFD) on Saudi children and their families.MethodsA cross-sectional study was conducted in which an online questionnaire was sent to all families registered in the Saudi celiac patients support group. We included only children (age 18 years of age and younger) with biopsy-confirmed celiac disease (CD).ResultsA total of 113 children were included in the final analysis, the median age was 9.9 years; 62.8% were females. One hundred (88.5%) of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 12 publications
0
24
0
3
Order By: Relevance
“…The observation of girls only suggests the conclusion that there were differences between groups in every scale, except in the physical health scale, and the observation of boys showed no differences only in emotional functioning and physical health. The results of other researchers are contradictory, some indicated that there is no difference between boys and girls [21,22], but there are also studies presenting lower quality of life in girls with coeliac disease [23,24].…”
Section: Discussionmentioning
confidence: 93%
“…The observation of girls only suggests the conclusion that there were differences between groups in every scale, except in the physical health scale, and the observation of boys showed no differences only in emotional functioning and physical health. The results of other researchers are contradictory, some indicated that there is no difference between boys and girls [21,22], but there are also studies presenting lower quality of life in girls with coeliac disease [23,24].…”
Section: Discussionmentioning
confidence: 93%
“…As the naturally GF grains and flours (e.g., quinoa, millet, teff, sorghum, buckwheat) are not mainstream items, the cost of the GF products is often more expensive than their gluten containing counterpart. The economic burden of the GFD has been previously documented in the United States (U.S.) [ 2 ], in Europe, Canada, Saudi Arabia, Iran and Chile [ 3 , 4 , 5 , 6 , 7 , 8 ]. However, with the onset of mainstream food manufacturers entering the GF market, a more recent evaluation of the cost and availability differences between GF products and their wheat-based counterparts is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the daily amount of tolerable gluten is in constant among people but consumption of less than 10 mg of gluten per day has been stated to be safe for patients with celiac disease. A cross-sectional study was conducted in which an online questionnaire to all families registered in the Saudi celiac patients support group, showing a significant negative socio-economic impact of GFD on children with CD & their families [10].…”
Section: Introductionmentioning
confidence: 99%